2021
DOI: 10.3390/ijns7020024
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Screening for Krabbe Disease—Illinois Experience: Role of Psychosine in Diagnosis of the Disease

Abstract: Population-based newborn screening for Krabbe disease was initiated by measurement of galactocerebrosidase (GALC) activity in the state of Illinois in December 2017. Due to the poor specificity of GALC for the diagnosis of Krabbe disease, second-tier testing services were provided to reduce the false positive rates for disease monitoring. Using ultra-pressure liquid chromatography coupled to mass spectrometry assay, a total of 497,147 newborns were screened. In total, 288 infants’ specimens (0.06%) having redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…In individuals with a psychosine concentration over 2 nmol/L, mutation analysis and neuro-diagnostic studies may be indicated, but it is not a first priority [17,18].…”
Section: Relationship Between Measured Galc Activity and Phenotypementioning
confidence: 99%
See 2 more Smart Citations
“…In individuals with a psychosine concentration over 2 nmol/L, mutation analysis and neuro-diagnostic studies may be indicated, but it is not a first priority [17,18].…”
Section: Relationship Between Measured Galc Activity and Phenotypementioning
confidence: 99%
“…Values under 2 nmol/L indicate that the individual probably will not develop Krabbe disease. In individuals with a psychosine concentration over 2 nmol/L, mutation analysis and neurodiagnostic studies may be indicated, but it is not a first priority [17,18].…”
Section: Relationship Between Measured Galc Activity and Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…Dear readers: I am proud to say that we are continuing to publish many important papers on newborn screening in IJNS , and the papers published in this issue clearly support my statement. Please allow me to highlight two papers published by Basheeruddin et al [ 1 ] and Corre et al [ 2 ] on newborn screening for Krabbe disease (KD) in this issue. Much more information is needed regarding this rare disease to inform discussion among researchers, clinicians and public advocates about whether it should be included as a part of the federal RUSP in the United States.…”
mentioning
confidence: 99%
“…The first paper by Basheeruddin et al [ 1 ] presents three years of Krabbe NBS experience in Illinois and discusses the results of analyzing psychosine as a second-tier test. The Illinois state NBS program performs GALC enzyme test as a first-tier assay and adds genetic tests with analyses of psychosine levels when newborns have low GALC enzyme levels.…”
mentioning
confidence: 99%